2021
DOI: 10.1016/j.xcrm.2021.100253
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decline of neutralizing antibodies is associated with decay of IgM in adults recovered from mild COVID-19

Abstract: The fate of protective immunity following mild severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection remains ill defined. Here, we characterize antibody responses in a cohort of participants recovered from mild SARS-CoV-2 infection with follow-up to 6 months. We measure immunoglobulin A (IgA), IgM, and IgG binding and avidity to viral antigens and assess neutralizing antibody responses over time. Furthermore, we correlate the effect of fever, gender, age, and time since symptom onset with anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 46 publications
8
52
1
Order By: Relevance
“…As expected, anti-S IgM, IgG and IgA titers declined over time and anti-S IgG becomes the major isotype at late convalescence (24,(50)(51)(52). In this study, IgA titers were the most affected over time.…”
Section: Discussionsupporting
confidence: 76%
“…As expected, anti-S IgM, IgG and IgA titers declined over time and anti-S IgG becomes the major isotype at late convalescence (24,(50)(51)(52). In this study, IgA titers were the most affected over time.…”
Section: Discussionsupporting
confidence: 76%
“…Similarly to other studies, we found that older individuals have higher anti-S-RBD IgG peak levels after infection compared with younger adults [ 18 , 19 ]. However, such association with age has not been consistently found, as in other studies higher anti-S-RBD IgG correlates with the presence of fever or severity of symptoms instead [ 17 , 20 ]. In our previous study, we also found that after adjusting for age, time since positive PCR-test and sex, hospitalised patients or those with fever had higher anti-RBD IgG levels than those not hospitalized or without fever [ 5 ].…”
Section: Discussionmentioning
confidence: 89%
“…However, as 73.6% of COVID-19 cases confirmed by 7 February 2021, in Estonia had occurred since 1 December 2020 [ 1 ], i.e. within a timeframe of >6 months when anti-S-RBD IgG should persist at detectable levels [ 17 ], we believe that waning immunity may have only minor impact on the seroprevalence estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in SARS-CoV-1 demonstrated that, although specific IgG antibodies and memory B-cells were undetectable after a 6-year follow-up, specific T-cell anamnestic response was maintained in a significant proportion of cases [ 39 ]. When evaluating neutralizating antibodies, Harrington et al recently demonstrated a rapid decline in these antibodies in patients recovered from Covid-19 [ 40 ]. Further studies with longer follow-up and ideally assessing the role of both cellular and humoral immunity are essential to developing optimal vaccine strategies.…”
Section: Discussionmentioning
confidence: 99%